Navigating the Regulatory Landscape: What are FDA Regulations for AI Medical Devices? - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2023)
Navigating the Regulatory Landscape: What are FDA Regulations for AI Medical Devices? The integration of Artificial Intelligence (AI) and Machine Learni...
Keywords: Digital Health; Diagnostics; Artificial Intelligence; Healthcare Innovation; Patient Care